Morphometrics and Reproductive Characteristics of the Freshwater Crab Sartoriana spinigera from the Habitat of Ratargul Swamp Forest, Bangladesh: An Approach to Conservation - Sanjida Akther; Mohammad Amzad Hossain; Debasish Pandit; Thouhidur Rahman Chowdhury; Sohel Mian (Scientifica)
A total of 332 freshwater crab Sartoriana spinigera samples were collected for eight consecutive months from the Ratargul freshwater swamp forest, Bangladesh, to examine their general morphometrics and reproductive traits. The length-weight relationships of carapace weight with carapace length, width, and depth indicated negative allometric growth. The logarithmic relationship between carapace weight and carapace length, carapace weight and carapace width, and carapace weight and carapace depth exhibited a correlation value of 0.86, 0.79, and 0.56, respectively. Fulton’s condition factor and allometric condition factor were found to be highest in March and lowest in October. The sex ratio was 1.59 : 1 for the male to female, which did not show a considerable divergence from the expected 1 : 1 ratio in the chi-square test (P<0.05). In July, a maximum of mature individuals was collected and investigated. The fertilization was 1297 ± 629 ova, the ovary weight was 447.22 ± 359.39 mg, and the egg diameter was 375.15 ± 130.18 µm. Histological analysis showed that the male hepatopancreas was well organized and decomposition was reported in the female during the vitellogenic stages of the ovary. Spermatogonium cells were found in the male gonad, and cells from the female gonad were in the vitellogenic mature stage. In conclusion, the research will serve as a foundation for future research work on freshwater crab species as well as the conservation and maintenance of the ecological balance of this species in the Ratargul freshwater swamp forest.